2021
DOI: 10.1002/chem.202101320
|View full text |Cite
|
Sign up to set email alerts
|

Polythiolactone‐Decorated Silica Particles: A Versatile Approach for Surface Functionalization, Catalysis and Encapsulation

Abstract: Invited for the cover of this issue is the group of Bart Jan Ravoo at Westfälische Wilhelms‐Universität Münster. The image depicts the “universal” post‐modification of silica particles coated with a polythiolactone polymer shell. Read the full text of the article at 10.1002/chem.202100547.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
2
1
Order By: Relevance
“…This also corresponds well to our previously published work where similar conditions were employed to decorate silica particles . Compared to the work published by Patton et al., we did not observe a swelling of the brushes after post-modification, as shown in Figure D.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…This also corresponds well to our previously published work where similar conditions were employed to decorate silica particles . Compared to the work published by Patton et al., we did not observe a swelling of the brushes after post-modification, as shown in Figure D.…”
Section: Resultssupporting
confidence: 93%
“…This also corresponds well to our previously published work where similar conditions were employed to decorate silica particles. 57 Compared to the work published by Patton et al, 56 we did not observe a swelling of the brushes after postmodification, as shown in Figure 1D. This difference is probably due to the lower ratio of thiolactone units available for the reaction compared to the homopolymers of Patton et al…”
Section: ■ Results and Discussioncontrasting
confidence: 66%
See 2 more Smart Citations